The Concept of Pious Children's Education in The Book Golden Ways Children Sholeh by Zainal Abidin bin Samsudin and Its Relevance To the Character of Adolescents - Panggi, Fadlian; N. Hula, Ibnu Rawandhy; Wantu, Hasyim Mahmud (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2024)
Damage to the character of children is caused by their distance from religious teachings and their lack of understanding of behaviour by Sharia. This study aims to determine the concept of pious child education in the book Golden Ways Children Sholeh by Zainal Abidin Bin Syamsuddin and its relevance to forming adolescent characters. This study used data collection techniques for library research and documentation studies. And analysis techniques using content analysis (content analysis). The results showed that the concept of pious children's education in the book Golden Ways Children Sholeh by Zainal Abidin Bin Syamsuddin refers to strengthening faith in children from an early age, such as certifying Allah Subhanah Wa ta'alah and familiarizing children to worship Allah. Some characteristics of pious children in the book Golden Ways of Sholeh Children include worshipping properly, praying diligently, loving the house of God, being fond of Infaq and giving alms.